EFFECT OF CROSS‐BORDER HEALTH CARE ON QUALITY AND PROGRESSIVITY OF FINANCING. Issue 1 (18th July 2019) - Aiura, Hiroshi
Abstract : In this study, we examine the effect of cross‐border health care in terms of public health insurance. We consider its effect on healthcare quality and progressivity of financing. We use a two‐country Hotelling model in which consumers are divided into two groups: high and low innate‐talent consumers. Aiming to maximize social welfare, governments impose a progressive income tax on consumers to provide healthcare services. Assuming that a payment scheme for healthcare services is based on diagnosis‐related group pricing, which has been adapted in many countries, we obtain the following results. The promotion of cross‐border health care does not influence healthcare quality or the progressivity of financing in patient‐importing countries, but does reduce healthcare quality and influence the progressivity of financing in patient‐exporting countries.